PENGARUH TIPE KEPEMIMPINAN DAN ORIENTASI PRESIDEN JOKOWI TERHADAP KEBIJAKAN HILIRISASI MINERAL BAUKSIT TAHUN 2019-2024 - Ghari Fazulur Rahman Nur Hamjah (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2025)
The raw bauxite export ban is one of Jokowi's breakthroughs in his efforts to downstream the mineral and coal industry. Despite being prosecuted by the European Union to the WTO at the time of the implementation of the raw nickel export ban, President Jokowi remains steadfast downstream to increase selling value and achieve natural resource sovereignty. Jokowi continues his program and believes that downstreaming can bring Indonesia into a developed country. This study aims to analyze President Jokowi's idiosyncratic factors in making Indonesia's international trade policy regarding the bauxite ore export ban as one of the steps in realizing downstreaming. This research uses a qualitative method with Margaret G Hermann's idiosyncratic approach through data obtained from content analysis on the internet. The results of this study based on Margaret G Hermann's Idiosyncratic theory, show that the bauxite export ban and downstreaming policies implemented by President Jokowi reflect that he has personality characteristics with an aggressive type and independent orientation but still shows openness to foreign investment in smelter construction and industrial supporting infrastructure which reflects flexibility in his foreign policy approach. For future research, it is recommended to conduct a more in-depth study by expanding the object of study to other leaders in the context of Indonesia's foreign policy and conducting quantitative data-based studies as well as further exploration of international responses to this policy to provide a more comprehensive understanding of the dynamics of global trade and Indonesia's economic diplomacy.